Feeling the Pain Down Memory Lane: On-going Trauma in Octavia E. Buttler’s Kindred - Rarastesa, Zita (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2023)
This paper attempts to discuss the ongoing Trauma of slavery as the collective Trauma for African American people in the US. It not only investigates the memory of Trauma experienced by the main character, Dana, in the novel Kindred but also describes how the author recalls the memory of the traumatic event and expresses it in the novel through a series of events the main character encountered. Although the traumatic event itself has long gone in the past, the memory of it still haunts the African American people through what Dana is going through. The narrative technique Butler uses in the novel is intriguing that she tells the story as some time machine where the main character can go back and forth from the setting of time, the 1970s, to the 19th-century slavery era. Furthermore, Dana experienced a physical injury that was incomprehensible for people in the 1970s to see as a result of the event that happened in the 19th-century slavery era. This can be seen as a reflection of the way African American people feel about slavery and the aftermath of it in the present. The traumatic event has passed, but the pain stays the same because ongoing racism against African American people remains.